Waterwheel wheel driving mechanism - ZHU DEJIN (2015)
The invention discloses a waterwheel wheel driving mechanism. The waterwheel wheel driving mechanism comprises a driving casing, the external surface of the driving casing is provided with driving teeth, the driving casing is provided with a driving groove in the axial direction, the driving groove is provided with a driving cylinder, one end of the driving cylinder is provided with a first driving ring, the other end of the driving cylinder is provided with a second driving ring, and the first driving ring and the second driving ring are arranged in parallel. According to the invention, the waterwheel wheel driving mechanism can be in butt joint with a driving shaft through the driving cylinder, the first driving ring and the second driving ring conveniently, the driving shaft can control the driving mechanism to rotate, the driving casing is in butt joint with a waterwheel wheel, and therefore the waterwheel wheel can be driven conveniently.